Land Use and Land Cover Changes in the Owabi Reservoir Catchment, Ghana: Implications for Livelihoods and Management - Antwi-Agyei Philip; Kpenekuu Felix; Hogarh ,Jonathan N.; Obiri-Danso Kwasi; Abaidoo R. C; Jeppesen Erik; Andersen Mathias Neumann (MDPI, 2023)
This article is Published by MDPI, 2019 and is also available at doi:10.3390/geosciences9070286